Esoteric Beliefs and Opposition to Corona Restrictions in Germany - Nils B. Weidmann (Politische Vierteljahresschrift, 2023)
Governmental measures against the spread of the Corona virus have been met with varying levels of opposition in many countries worldwide. Existing research has claimed that some of this opposition is linked to esoteric and anthroposophical beliefs. This research note tests this in an observational study using election results from the 2021 parliamentary election in Germany and new data on the distribution of natural healers, homeopathic doctors and Steiner schools. Results show that counter to common expectations, there is no evidence that esoteric beliefs systematically lead to increased support for the established right-wing AFD . Rather, some indicators for esoteric beliefs – in particular, the presence of homeopathic doctors and Waldorf schools – are related to higher support for the new fringe party dieBasis , a~single-issue party campaigning against governmental Corona measures.
Keywords: 320; Esoteric beliefs; Homeopathy; Corona measures; Spatial analysis; Esoterische Überzeugungen; Homöopathie; Corona-Maßnahmen; Räumliche Analyse